Are movement-based classification systems more effective than therapeutic exercise or guideline based care in improving outcomes for patients with chronic low back pain? A systematic review. (1st January 2019) - Riley, Sean P.; Swanson, Brian T.; Dyer, Elizabeth
ABSTRACT: Objectives : The purpose of this systematic review was to determine if movement-based classification (MBC) systems are more effective than therapeutic exercise or guideline-based care (GBC) in improving outcomes in patients with low back pain (LBP) based upon randomized clinical trials (RCT) with moderate to high methodological quality and low to moderate risk of bias. Methods : The search strategy was developed by a librarian experienced in systematic review methodology and peer reviewed by a second research librarian. The following databases were searched from their inception to May 17, 2018: PubMed, Embase, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and the WHO International Clinical Trials Registry Platform. The identified RCTs with a PEDro score of ≥6 were screened and assessed for risk of bias by two blinded individual reviewers using Covidence. Results : Seven studies were identified that had moderate-to-high methodological quality. One of the studies was identified as having a high risk of bias. Of the six studies that remained, only one study reported finding a statistically significant difference at the immediate follow-up that was not clinically significant. There was no significance at 6 and 12 months. Discussion : There is a paucity of moderate to high methodological quality RCTs with similar methodology that compare MBC to standard of care treatments for patients with LBP. Studies with moderate to high methodological quality that have a low risk of bias do not support MBCs as being superior to general exercise or GBC in the treatment of nonradicular LBP. Level of Evidence : 1a